Chromoselective Photocatalysis Enables Stereocomplementary Biocatalytic Pathways. (26th February 2021) - Schmermund, Luca; Reischauer, Susanne; Bierbaumer, Sarah; Winkler, Christoph K.; Diaz‐Rodriguez, Alba; Edwards, Lee J.; Kara, Selin; Mielke, Tamara; Cartwright, Jared; Grogan, Gideon; Pieber, Bartholomäus; Kroutil, Wolfgang
Abstract: Controlling the selectivity of a chemical reaction with external stimuli is common in thermal processes, but rare in visible‐light photocatalysis. Here we show that the redox potential of a carbon nitride photocatalyst (CN‐OA‐m) can be tuned by changing the irradiation wavelength to generate electron holes with different oxidation potentials. This tuning was the key to realizing photo‐chemo‐enzymatic cascades that give either the ( S )‐ or the ( R )‐enantiomer of phenylethanol. In combination with an unspecific peroxygenase from Agrocybe aegerita, green light irradiation of CN‐OA‐m led to the enantioselective hydroxylation of ethylbenzene to ( R )‐1‐phenylethanol (99 % ee ). In contrast, blue light irradiation triggered the photocatalytic oxidation of ethylbenzene to acetophenone, which in turn was enantioselectively reduced with an alcohol dehydrogenase from Rhodococcus ruber to form ( S )‐1‐phenylethanol (93 % ee ). Abstract : Green or blue? The wavelength controls the outcome. Chromoselective activation of a carbon nitride generates electron holes with different oxidation potentials that are used for selective oxidation processes. By coupling the photocatalytic reactions with biocatalysis the ( S )‐ or the ( R )‐enantiomer of 1‐phenylethanol was synthesized stereoselectively.